Limitations and mechanisms influencing the migratory performance of soaring birds. (January 2016) - Miller, Tricia A.; Brooks, Robert P.; Lanzone, Michael J.; Brandes, David; Cooper, Jeff; Tremblay, Junior A.; Wilhelm, Jay; Duerr, Adam; Katzner, Todd E.
Abstract : Migration is costly in terms of time, energy and safety. Optimal migration theory suggests that individual migratory birds will choose between these three costs depending on their motivation and available resources. To test hypotheses about use of migratory strategies by large soaring birds, we used GPS telemetry to track 18 adult, 13 sub‐adult and 15 juvenile Golden Eagles Aquila chrysaetos in eastern North America. Each age‐class had potentially different motivations during migration. During spring, the migratory performance (defined here as the directness of migratory flight) of adults was higher than that of any other age‐classes. Adults also departed earlier and spent less time migrating. Together, these patterns suggest that adults were primarily time‐limited and the other two age‐classes were energy‐limited. However, adults that migrated the longest distances during spring also appeared to take advantage of energy‐conservation strategies such as decreasing their compensation for wind drift. During autumn, birds of all age‐classes were primarily energy‐minimizers; they increased the length of stopovers, flew less direct routes and migrated at a slower pace than during spring. Nonetheless, birds that departed later in autumn flew more directly, indicating that time limitations may have affected their decision‐making. During both seasons, juveniles had the lowest performance, sub‐adults intermediate performance and adults the highest performance. Our results show age‐ and seasonal variation in time and energy‐minimization strategies that are not necessarily exclusive of one another. Beyond time and energy, a complex suite of factors, including weather, experience and navigation ability, influences migratory performance and decision‐making.